Application of Fish Waste Processing for Sustainable Livestock Feed Production A Community Engagement Study in Garut Regency - Lianingsih, Nestia; Suhaimi, Nurnisaa binti Abdullah; Prabowo, Agung (Research Collaboration Community (RCC), 2024)
This community engagement study aimed to develop an application for processing fish waste into animal feed based in an incubator system in Garut Regency. The program was conducted from May to November 2023 with the primary objective of transferring technology in waste processing and animal feed production to partner groups. Methods included socialization, technical and non-technical training, and direct mentoring in animal feed pellet production. Results showed a significant improvement in the knowledge and skills of the groups in producing fish waste pellets, reducing feed production costs, and enhancing the sustainability of local livestock businesses. Challenges encountered included initial production limitations and consumer trust in new products. With in-depth scientific approaches and sustained support, the program successfully created positive impacts on the environment and community economic welfare.